The Patterns of Ownership and the Registration of Customary Land in Manggarai Regency, Indonesia - Mujiburohman, Dian Aries; Andari, Dwi Wulan Titik; Junarto, Rohmat; Mujiati, Mujiati (SCAD Independent, 2024)
This research analyzes ownership patterns and the process of legalizing customary land in Manggarai Regency. The research method used is qualitative with a descriptive approach and uses secondary data. Normative socio-juridical methods are also used to view and analyze the research data that has been collected. Data was collected through observations and interviews with traditional elders and members of traditional communities. The results showed that the legalization of Ulayat land greatly affected the pattern of land ownership in Manggarai and the change of entities from indigenous land to non-indigenous land that was initially jointly controlled or communal into individual rights due to the legalization or registration of land. Legalization of Ulayat land with a public dimension can only be done by measuring, mapping, and recording it in the land register. Meanwhile, Ulayat land with private dimensions can be issued a land certificate for individuals with a release mechanism from the customary leader to be used as state land. This legalization resulted in the depreciation of Ulayat land and the fading of customary bonds in Manggarai. This research provides insight into land legalization's legal and social impacts on Manggarai, highlighting significant changes in ownership structures and the loss of customary values.